Evaluation of the cytotoxic activity of essential oils from Malaysian herbal plants against A375 and A431 skin cancer cell lines - Jawahar, Bassam Mohamed; Shahbuddin, Munira; Ridzwan, Irna Elina; Abu Bakar, Mohd Rushdi (2024)
Skin cancer incidences is rising due to prolonged harmful exposure to UV rays. Current therapies can adversely affect healthy cells. Conventional chemotherapy administered orally and intravenously poses risks of off targets, leading to severe and debilitating side effects. This study explored the anticancer potential of essential oils (EOs) extracted by hydrodistillation from seven local plant leaves (Piper betle, Persicaria minor, Cosmos caudatus, Citrus aurantifolia, Citrus hystrix, Citrus microcarpa, and Piper sarmentosum) on melanoma (A375), non-melanoma (A431), and fibroblasts skin cells (HFF1). Cytotoxicity assessment using MTT assay showed that all EOs tested had inhibitory effects of all EOs towards both cancer cell lines. Out of all seven plant EOs tested, P. sarmentosum EO displayed the most potent cytotoxicity at 80 ± 0.27 μg/mL with the extraction yield of 0.63%. Morphological changes in cellular size were observed after 4 h of EO treatment, leading to cell death coherently with declination of viability. This research signifies Malaysian plant’s role for topical application, as demonstrated by viability and morphology study.